Chemiresistors: Catalytic Metal Nanoparticles Embedded in Conductive Metal–Organic Frameworks for Chemiresistors: Highly Active and Conductive Porous Materials (Adv. Sci. 21/2019) - Koo, Won‐Tae (Adv Sci (Weinh), 2019)
In article number https://doi.org/10.1002/advs.201900250, Il‐Doo Kim and co‐workers develop ultra‐small and well‐dispersed metal nanoparticles (NPs) embedded in the cavities of conductive metal–organic frameworks (C‐MOFs). The unique porous structure of C‐MOFs inhibits bulk growth of metal NPs, generating highly active and porous conductive materials. The catalytic metal NPs‐loaded C‐MOFs exhibit improved NO(2) sensing performance, due to the synergistic effect of catalytic metal NPs and C‐MOFs. [Image: see text]